Sistem Informasi Pelayanan Perawatan Pasien Berbasis Web Pada Klinik Cahaya Ibu - Riski Annisa; Weiskhy Steven Dharmawan; Chika Suhendra (Jurnal Sistem Informasi, 2023)
Information technology in the world is developing very fast. This is supported by the existence of electronic devices such as laptops, telephones and others, with these tools can help facilitate all human affairs to complete their work. Likewise with Cahaya Ibu 1 Clinic, in its service, patients definitely need fast and satisfying services for patients who seek outpatient or inpatient treatment. Therefore, the author tries to make research on the web-based patient care service system at Cahaya Ibu 1 Clinic. At this time, Cahaya Ibu 1 Clinic is one of the private clinics in the city of Pontianak. The system here is still using manually, which is still using books in recording patient registration, writing medical records, to making reports. This may slow down the work and may cause errors in the recording. The information system created by the author in this final project can solve the problems that exist in this clinic, as well as with a computerized system that is expected to facilitate the work of the employees there and an effective and efficient activity can be achieved. With the passage of time so that patients do not have to wait long and will look more conducive.